Quadriceps oxygenation during isometric exercise in sailing - Vogiatzis, I.; Tzineris, D.; Athanasopoulos, D.; Georgiadou, O.; Geladas, N. (International Journal of Sports Medicine, 2008)
The aim of the present study was to investigate why blood lactate after prolonged quadriceps contraction during hiking is only marginally increased. Eight sailors performed five 3-min hiking bouts interspersed with 5-s recovery periods. Whole body oxygen uptake, heart rate and lactate were recorded, along with continuous-wave near-infrared spectroscopy measures of quadriceps oxygenation. The time for 50 % re-oxygenation was also assessed as an indication of the degree of localized oxygen delivery stress. Hiking elicited a significant (p = 0.001) increase in mean (± SD) heart rate (124 ± 10 beats · min-1) which was accompanied by a disproportionately low oxygen uptake (12 ± 2 ml · kg-1 · min-1). Lactate was significantly (p = 0.001) increased throughout hiking manoeuvres, though post-exercise it remained low (3.2 ± 0.9 mmol · l-1). During the hiking bouts mean quadriceps oxygenation was significantly (p = 0.001) reduced compared to baseline (by 33 ± 5 %), indicating an imbalance between muscle oxygen accessibility and oxygen demand. During rest intervals quadriceps oxygenation was partially restored. After the end of the final bout the time for 50 % re-oxygenation was only 8 ± 2 s, whereas recovery of quadriceps oxygenation and oxygen uptake was completed within 3 min. We conclude that the observed low lactate could be attributed to the small oxygen and energy deficits during hiking as the muscles' oxygen accessibility is presumably partially restored during the brief rest intervals.